2019
DOI: 10.7150/jca.33063
|View full text |Cite
|
Sign up to set email alerts
|

Association of the TP53 rs1042522 C>G polymorphism and hepatoblastoma risk in Chinese children

Abstract: The TP53 gene encodes an important class of cell cycle and tumor-suppressing factors that play critical roles in maintaining genomic stability. The TP53 Arg72Pro (rs1042522 C>G) polymorphism has been reported to be associated with the risk of several types of adult cancers; however, its risk for pediatric cancers remains unclear. Here, we analyzed the association of the TP53 gene rs1042522 C>G polymorphism with hepatoblastoma (HB) susceptibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 50 publications
0
17
1
Order By: Relevance
“…Details of the selection of subjects and collection of specimens have been published elsewhere [ 22 , 23 ]. This is a collaborative study with hepatoblastoma cases and controls enrolled from eight hospitals in China.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of the selection of subjects and collection of specimens have been published elsewhere [ 22 , 23 ]. This is a collaborative study with hepatoblastoma cases and controls enrolled from eight hospitals in China.…”
Section: Methodsmentioning
confidence: 99%
“…To discover more variants predicting the risk of hepatoblastoma, here we conducted a multicenter case-control study among children of Chinese ancestry. [22,23]. is is a collaborative study with hepatoblastoma cases and controls enrolled from eight hospitals in China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of subjects could be found in the previously published studies. 15,16 The study protocol was permitted by the Ethics Committee of each participating hospital (Ethical approve number: 2017120101). This study was conducted in accordance with the Declaration of Helsinki.…”
Section: Study Subjectsmentioning
confidence: 99%
“…[9][10][11][12] A few epidemiological reports have indicated that single nucleotide polymorphisms (SNPs) might also be predisposing factors for hepatoblastoma. [13][14][15][16] However, it is difficult to obtain a significant association owing to the scarcity of included patients. Therefore, unveiling the underlying etiology of hepatoblastoma using a larger sample size, especially causative genetic factors, is of great significance.…”
Section: Introductionmentioning
confidence: 99%